2015
DOI: 10.1299/transjsme.14-00423
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ammonia/N<sub>2</sub>/O<sub>2</sub> laminar flame in oxygen-enriched air condition

Abstract: Ammonia is regarded as one of the alternative fuels and regarded as a "hydrogen carrier". Ammonia is an easily-liquefiable fuel. Therefore, it is a suitable fuel for transportation and storage. Also, ammonia can be produced in large quantities by using the Haber-Bosch process with low price. It is known that the laminar burning velocity of ammonia/air mixture is about 10 cm/s at near stoichiometric condition. This laminar burning velocity is very low compared with that of other fossil fuels. Therefore, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…The experimental results showed that the flame propagation speeds are lower than those of CH 4 /air flames at the O 2 concentration of 0.35. It is different from the results of Takeishi et al, which indicated that the laminar burning velocities at the O 2 concentration of 0.35 are almost the same as those of CH 4 /air flames (Takeishi et al, 2015). In addition, they constructed a model of ammonia combustion with 38 species and 265 reactions, which can predict the results with a favorable satisfaction.…”
Section: Frontiers In Energycontrasting
confidence: 62%
See 2 more Smart Citations
“…The experimental results showed that the flame propagation speeds are lower than those of CH 4 /air flames at the O 2 concentration of 0.35. It is different from the results of Takeishi et al, which indicated that the laminar burning velocities at the O 2 concentration of 0.35 are almost the same as those of CH 4 /air flames (Takeishi et al, 2015). In addition, they constructed a model of ammonia combustion with 38 species and 265 reactions, which can predict the results with a favorable satisfaction.…”
Section: Frontiers In Energycontrasting
confidence: 62%
“…Oxygen enriched combustion can be considered as a promising approach to increase burning velocity. The experimental results measured by Takeishi are shown in Figure 6 (Takeishi et al, 2015). It can be observed that the velocities can be close to those of CH 4 /air flames when the O 2 concentration up to 0.35 and the maximum velocity improves to 36.1 cm/s, which is around 5 times the value measured under the air condition.…”
Section: Frontiers In Energymentioning
confidence: 63%
See 1 more Smart Citation
“…48 Nevertheless, relevant studies on this topic are still currently limited. Takeishi et al 27 experimentally measured the S u 0 of oxygenenriched ammonia and found that the S u 0 of mixtures can reach the same level of hydrocarbon fuels when the fraction of O 2 in O 2 + N 2 is higher than 35%. However, since the experiment did not exclude the effect of the flame stretch, the reported S u 0 could be higher than actual values.…”
Section: Introductionmentioning
confidence: 99%
“…Takeishi et al investigated the LBV of ammonia under oxygen enriched conditions, and they indicated that the LBV of ammonia increases with increasing the concentration of oxygen . They also showed that the maximum value of LBV can be reached at the same level of that of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%